Mental, Neurological, and Somatic Comorbidities and Their Treatment in Persons With Intellectual Disability - Weih, Markus; Koehler, Sabine; Schoell, Norbert; Schulz, Mandy; Hering, Ramona (Deutsches Ärzteblatt international, 2022)
Background: Persons with intellectual disability (ID) often suffer from significant comorbidities. As data have been lacking until now, the present report is the first one containing outpatient data on the prevalence of ID in Germany, its comorbidities, and outpatient (drug) treatment.Methods: This study is based on the nationwide outpatient billing data and drug pre-scription data of all SHI-insured adults (SHI, statutory health insurance) (age 18-109) who were seen at least once in an outpatient medical practice in 2018. Patients with at least two F70-F79 diagnoses in two quarters were included in the study group (SG) (n = 324 428). A random sample of patients without ID served as the control/comparison group (CG) (n = 648 856). The odds ratios (SG vs. CG) for comorbidities, prescriptions of selected classes of drugs, and involvement of medi-cal specialties were each analyzed by multivariate logistic regression.Results: The prevalence of ID was 0.55%. ID was found to be associated with a variety of comorbidities. The highest odds ratios [OR] were for infantile cerebral palsy (OR: 121.71; 95% confidence interval: [111.67; 132.67]), autism spectrum dis-orders (OR: 83.85 [75.54; 93.08]), and developmental disabilities (OR: 61.34 [58.86; 63.94]). The most frequently prescribed drug categories (as classified by the anatomic-therapeutic-chemical (ATC) convention) were psychoactive drugs (anti -psychotic, anxiolytic, and hypnotic drugs and sedatives) and antiepileptic drugs (OR: 10.40 [10.27; 10.53] and 9.90 [9.75; 10.05], respectively). Both general practi-tioners (OR: 2.64 [2.59; 2.69]) and medical specialists were consulted by the SG more frequently than by the CG; the type of specialist most commonly consulted was in the neuropsychiatric field, i.e., a neurologist or psychiatrist (OR: 6.85 [6.77; 6.92]).Conclusion: A diagnosis of ID frequently appears in outpatient billing data. Future analyses should be devoted to the specific care of people with intellectual disability, who constitute an especially multimorbid and vulnerable patient group.
CRIS-Team WoS Importer:2022-10-07